Pengaruh Opini Audit, Belanja Modal, Pendapatan Asli Daerah, dan Dana Perimbangan Terhadap Kinerja Keuangan Pemerintah Kabupaten/Kota di Provinsi Bali Tahun 2015-2019 - Suandani, Kadek Peni; Astawa, Gede Putu Banu (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of audit opinion, capital expenditure, local revenue and balance funds on financial performance. This study uses a quantitative approach using instruments in its measurement and statistical processing. This research was conducted in regencies / cities in Bali Province. The population in this study were all districtsÂ / cities in Bali Province with 8 districts and 1 municipality. The Budget Realization Report that will be studied is in 2015-2019 or for five years, so that the total population in this study is 45 reports. The sample was taken using the total sampling method, in order to obtain a sample of 45. The data of this study were collected using the documentation method which was then processed by multiple linear regression analysis with the help of SPSS.The results of the study state that audit opinion, capital expenditures, local revenue, general allocation funds, and special allocation funds have a positive effect on government financial performance.